Bio-engineered cell membrane nanovesicles as precision theranostics for perihilar cholangiocarcinoma. (25th February 2020) - Zhang, Xiaojie; Zhang, Yang; Zhang, Yunming; Lv, Peng; Zhang, Pengfei; Chu, Chengchao; Mao, Jingsong; Wang, Xiaoyong; Li, Wengang; Liu, Gang
Abstract : We engineered a human epidermal growth factor receptor 2 (HER2) affibody to the surface of cell membrane nanovesicles (A-NVs) in a ligand-oriented manner and loaded them with indocyanine green (ICG) as precision theranostics for PHCC treatment. Abstract : Perihilar cholangiocarcinoma (PHCC) presents a formidable challenge due to its occult anatomic location, aggressive growth, insensitivity to conventional chemotherapy, and poor prognosis. Herein, we engineered a human epidermal growth factor receptor 2 (HER2) affibody to the surface of cell membrane nanovesicles (A-NVs) in a ligand-oriented manner and loaded them with indocyanine green (ICG) as precision theranostics for PHCC treatment. The A-NVs@ICG were prepared and exhibited satisfactory targeting effects in HER2-overexpressing PHCC cells. In vivo fluorescence and photoacoustic imaging demonstrated that A-NVs@ICG promoted the accumulation of ICG in PHCC tissue, leading to enhanced tumor regression and improved anti-cancer effects when combined with photoirradiation. Therefore, bio-engineered A-NVs@ICG represent a promising nanotheranostic agent for PHCC with potential for clinical translation.